2017
DOI: 10.3390/toxins9040141
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Mycotoxin Deoxynivalenol Using Microorganisms Isolated from Environmental Samples

Abstract: The trichothecene mycotoxin deoxynivalenol (DON) is a common contaminant of wheat, barley, and maize. New strategies are needed to reduce or eliminate DON in feed and food products. Microorganisms from plant and soil samples collected in Blacksburg, VA, USA, were screened by incubation in a mineral salt media containing 100 μg/mL DON and analysis by gas chromatography mass spectrometry (GC/MS). Two mixed cultures derived from soil samples consistently decreased DON levels in assays using DON as the sole carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 31 publications
(44 reference statements)
0
6
1
Order By: Relevance
“…The composition of LZ-N1 obtained in our study differed widely from that of other reported DON-detoxification consortia (Volkl et al, 2004; Yoshizawa et al, 2006; Ahad et al, 2017; Wilson et al, 2017). Many previously reported genera with DON-degrading ability were also found in LZ-N1.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…The composition of LZ-N1 obtained in our study differed widely from that of other reported DON-detoxification consortia (Volkl et al, 2004; Yoshizawa et al, 2006; Ahad et al, 2017; Wilson et al, 2017). Many previously reported genera with DON-degrading ability were also found in LZ-N1.…”
Section: Discussioncontrasting
confidence: 85%
“…Eleven genera accounted for 99.99% of the sequences, and Pseudomonas had the highest relative abundance (accounting for 44.98% of the sequences). The population structure of LZ-N1 bacterial consortium differed from the previously reported ones, which was able to effectively biodegrade DON into 3-epi-DON under aerobic condition, including the genera Acinetobacter , Leadbetterella , and Gemmata (Wilson et al, 2017). The raw reads of the consortium LZ-N1 were deposited into the NCBI Sequence Read Archive database (Accession Number: PRJNA557441; https://www.ncbi.nlm.nih.gov/bioproject/PRJNA557441).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…In the microbial culture of Islam et al [ 23 ], capable of biotransforming DON into DOM-1, Stenotrophomonas was also present, next to a high abundance of Serratia . Lastly, a microbial culture from soil capable of degrading DON into 3-keto-DON contained mostly members of the genera Acinetobacter , Leadbetterella and Gemmata [ 34 ], whereas Acinetobacter was also found in all four enrichments of product B. In addition, Sphingomonas was present in the third enrichment, which is known to degrade DON into 3-keto-DON, 3-epi-DON or 16-HDON [ 48 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wilson et al [ 7 ] reported the screening of plant and soil samples for microorganisms capable of degrading trichothecenes and eventually identified two mixed cultures consistently decreasing DON levels through oxidation to 3-keto-DON. Another study screened 43 bacterial isolates and identified Bacillus shackletonii L7, which is capable of reducing aflatoxin B1 (AFB 1 ), AFB 2 , and AFM 1 [ 8 ] where a thermostable-enzyme enriched in the culture’s supernatant was purified with an estimated molecular mass of 22 kDa.…”
mentioning
confidence: 99%